2016
DOI: 10.1371/journal.pone.0152528
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Distributed-Memory Particle Method Enables Acquisition-Rate Segmentation of Large Fluorescence Microscopy Images

Abstract: Modern fluorescence microscopy modalities, such as light-sheet microscopy, are capable of acquiring large three-dimensional images at high data rate. This creates a bottleneck in computational processing and analysis of the acquired images, as the rate of acquisition outpaces the speed of processing. Moreover, images can be so large that they do not fit the main memory of a single computer. We address both issues by developing a distributed parallel algorithm for segmentation of large fluorescence microscopy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 40 publications
0
18
0
1
Order By: Relevance
“…The source code of OpenFPM, virtual machines for various operating systems with a complete OpenFPM environment pre-installed, virtualized Docker containers, documentation, example applications, and tutorial videos are freely available from http://openfpm.mpi-cbg.de. We hope that the flexibility, free availability, performance, quality of documentation, and longterm support of OpenFPM will make it a standard platform for particles-only and hybrid particle-28 mesh simulations of discrete and continuous models on parallel computer hardware, as well as for non-simulation applications, such as evolutionary optimization strategies and particle-based image-analysis methods [83,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source code of OpenFPM, virtual machines for various operating systems with a complete OpenFPM environment pre-installed, virtualized Docker containers, documentation, example applications, and tutorial videos are freely available from http://openfpm.mpi-cbg.de. We hope that the flexibility, free availability, performance, quality of documentation, and longterm support of OpenFPM will make it a standard platform for particles-only and hybrid particle-28 mesh simulations of discrete and continuous models on parallel computer hardware, as well as for non-simulation applications, such as evolutionary optimization strategies and particle-based image-analysis methods [83,73].…”
Section: Discussionmentioning
confidence: 99%
“…One of the main advantages of OpenFPM over other simulation frameworks is that OpenFPM can transparently handle spaces of arbitrary dimension. This enables simulations in higherdimensional spaces, such as the four-dimensional spaces used in lattice quantum chromodynamics [71,72], and it also enables parallelization of non-simulation applications that require 25 high-dimensional spaces, including image analysis algorithms [73] and Monte-Carlo sampling strategies [74]. A particular Monte-Carlo sampler used for stochastic real-valued optimization is the Covariance-Matrix-Adaptation Evolution Strategy (CMA-ES) [75,76].…”
Section: Particle-swarm Covariance-matrix-adaptation Evolution Stratementioning
confidence: 99%
“…Their method was tested with human glioblastoma cell culture IF images and obtained high agreement with their manual GT. Finally, in a very recent article, Afshar et al [8] proposed a distributed-memory algorithm for segmentation where each boundary pixel is modeled as a particle system that evolves in time. Authors showed good results in synthetic images and in cell culture IF images.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors developed algorithms to automate IF analysis using unsupervised methods, mostly based on deformable contours and region-based approaches [2, 3, 4, 5, 6, 7, 8] and fewer focused on signal processing [9, 10]. Despite a great deal of publications in cell analyses, most of the methods for detecting and segmenting cells in IF images have been tailored to work with images derived from cell cultures or experimental animals, in which several parameters can be controlled to render IF images with a rather smooth, clean background and high contrast.…”
Section: Introductionmentioning
confidence: 99%
“…The pipeline shows efficient parallel scaling (Amdahl's Law, parallel fraction = 0.95) on up to 47 cores, achieving data rates of up to 1400 MB/second (SFigure 35). This enables real-time conversion of images to the APR, as it is faster than the acquisition rate of microscopes (32,33).…”
Section: Benchmarks On Real Datamentioning
confidence: 99%